BERAT DAN TINGGI BADAN ORANG TUA DENGAN STATUS GIZI BALITA DI KABUPATEN ACEH BESAR - Miko, Ampera; Al-Rahmad, Agus Hendra (PERSATUAN AHLI GIZI INDONESIA, 2017)
The nutritional status condition in Aceh district was opaque. According to some sources, the malnutrition of children under five years such as wasting, stunting, underweight and this problem has brought bad impact to the health problem. The problem of malnutrition is a cause of family characteristic and anthropometry factors of parents. The study design used was cross-sectional design conducted in Aceh Besar with a sample of households who have children. The research is using secondary and primary data PSG Aceh 2015, obtained through documentation study and processed. In the research result, there are height and weight relationships of parents with infant nutritional status based on indicators WFH and HFA (p<0,05), but not in maternal weight (p>0,05). Weight and height of the father shows the relationship (p<0,05) with nutritional status (WFA), but the mother's weight and height showed not to relationship (p>0,05). The conclusion, the high acute and chronic nutritional problems at Aceh Besar district is the result of factors anthropometric parents who role in the amount of malnutrition especially the weight and height of a father. Suggestion, the stakeholders can improve the condition of the economy and education to stem the problem of other nutrients found in the area of Aceh Besar.